Pengaturan Fungsi Dinas Pariwisata Kabupaten Lembata dalam Pengembangan Objek Pariwisata di Pulau Awulolong - Maria Oktafianti Palang Ledun; Kotan Y. Stefanus; Hernimus Ratu Udju (International Forum of Researchers and Lecturers, 2024)
Based on the author’s observations, the basic background of the problem can be formulated as follows: (1) How are functions regulated Lembata Regency Tourism Office in the Development of Tourism Objects on Awulolong Island: (2) What are the Inhibiting Factors in Implementing the Regulatory Functions of the Lembata Regency Tourism Office in the Development of Tourism Attrractions on Awulolong Island which is dosely related to the function the Department. In order to answer this question, research was carried out using the Qualitative Descriptive Analysis Method in accordance with the data obtained while still paying attention to theories, principles and legal rules. Therefore, this research that originates from primary, secondary and tertiary data using an empirical and juridical approach normative. The result of this research show that the regulation of the functions of the Lembata Regency Tourism Office in the development of tourism objects on Awulolong Island in accordance with Law Number 10 of 2009 concerning tourism and Lembata Regency Regional Regulation Number 1 of 2012 concerning the Lembata Regency Tourism Development Master plan has not been implemented properly. This can be seen from the failure of planned tourist destination development project to progress. Suggestions: (1) The Tourism Department is concerned with making designs that are button - up in nature so that the planned program are in line with the focus on the needs and interests of the community: (2) Increasing community participation in integrated and future – oriented or sustainable management to advance tourist areas: (3) Take firm action against all violationsthat do not comply with applicable rules and principles.